2014
DOI: 10.1177/0959683614538071
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation in peat deposits from northern Sweden to northern Germany during the last millennium

Abstract: Historic carbon accumulation rates in four bogs on a north to south transect from Sweden to Germany were calculated by using the bulk densities and carbon concentrations of 1-cm peat layers and a fine-resolution radiocarbon chronology. Carbon accumulation rates were compared to environmental data to explore the effects of climatic factors. Carbon accumulation rates in a period without clear human impact on the bog ecosystems ( c.ad 1700–ad 1800) ranged from 25 g C/m2/yr in the most northern site to 50 g C/m2/y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…They found that autogenic processes driven by the accumulation of organic matter have played a primary role in causing vegetation change from herbaceous (sedge-dominated) to Sphagnum-dominated peatlands, influencing carbon accumulation during the Holocene, while climate has played only a secondary, but important, role in changing species abundance. Van der Linden et al (2014) present peat-core analysis results from four bogs along a latitudinal gradient from northern Germany to northern Sweden to investigate climate influence on peat carbon accumulation during the last millennium. They found that southern sites have higher accumulation rates than northern sites, suggesting the importance of temperature in affecting carbon accumulation.…”
Section: Overviews Of Contributions To the Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…They found that autogenic processes driven by the accumulation of organic matter have played a primary role in causing vegetation change from herbaceous (sedge-dominated) to Sphagnum-dominated peatlands, influencing carbon accumulation during the Holocene, while climate has played only a secondary, but important, role in changing species abundance. Van der Linden et al (2014) present peat-core analysis results from four bogs along a latitudinal gradient from northern Germany to northern Sweden to investigate climate influence on peat carbon accumulation during the last millennium. They found that southern sites have higher accumulation rates than northern sites, suggesting the importance of temperature in affecting carbon accumulation.…”
Section: Overviews Of Contributions To the Special Issuementioning
confidence: 99%
“…Peatland extent is from Yu et al (2010). New peatland sites and regions discussed in the contributions of this Special Issue (shown as open boxes from western Europe to eastern Canada) are from 1 – Van der Linden et al (2014); 2 – Mathijssen et al (2014); 3 – Pluchon et al (2014); 4 – Zhao et al (2014); 5 – Nichols et al (2014); 6 – Yu et al (2014); 7 – Packalen and Finkelstein (2014); 8 – Holmquist and MacDonald (2014); 9 – Shiller et al (2014); 10 – Magnan and Garneau (2014); and 11 – Garneau et al (2014).…”
Section: Overviews Of Contributions To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The TOC/TN (C:N ratio) values are expressed as atomic ratios and were calculated to estimate the origin of the organic material (Meyers and Teranes, 2001). In addition, carbon accumulation rates (CAR, g C m −2 yr −1 ) were estimated for each depth where C concentration measurements were available according to van der Linden et al (2014): CAR = r × C × ρ , where r is the sediment accumulation rate, C is the carbon concentration and ρ is the bulk density.…”
Section: Methodsmentioning
confidence: 99%
“…Conifers replaced broadleaved deciduous species, which had been abundant during the Holocene thermal maximum (8000–5500 cal yr BP), apparently due to climatic cooling and increased land surface wetness (e.g., Seppä and Birks, 2001; Novenko et al, 2009b; Olchev and Novenko, 2011), in combination with increasing anthropogenic disturbance (Clear et al, 2015; Novenko et al, 2015). During recent decades, a large number of studies have explored the paleoecology of eastern Europe and European Russia, including studies focused on vegetation history, wetland development, and carbon accumulation by peatlands (Arslanov et al, 1999; Stančikaite et al, 2006; Niinemets and Saarse, 2009; Heikkilä and Seppä, 2010; Mauquoy et al, 2002; Mauquoy and Yeloff, 2008; Mitsch et al, 2013; Tuittila et al, 2014; van der Linden et al, 2014). Substantial knowledge gaps remain, however.…”
Section: Introductionmentioning
confidence: 99%